Estimando a prevalência da ingestão inadequada de nutrientes Estimating prevalence of inadequate nutrient intake - Betzabeth Slater; Dirce Lobo Marchioni; Regina Mara Fisberg (Universidade de São Paulo, 2004)
Na avaliação das dietas em um grupo de indivíduos, com freqüência é de interesse conhecer a proporção que apresenta ingestão acima ou abaixo de um determinado critério. Discute-se uma nova metodologia para estimar a prevalência de inadequação do consumo de nutrientes utilizando como valores de referência as DRIS - dietary reference intakes. Foram abordados os aspectos sobre a utilização de inquéritos alimentares baseados em métodos que permitam uma estimativa quantitativa a mais acurada possível, sendo necessárias medidas repetidas, em dias não consecutivos. O consumo alimentar é ajustado pelas variâncias intra e interpessoal, obtendo-se uma distribuição corrigida por esses valores. A partir da construção da curva de distribuição utilizando-se os parâmetros corrigidos estimados (média e desvio-padrão), pode-se utilizar o método EAR (estimate average requirement) como ponto de corte para verificar a proporção de indivíduos cuja ingestão do nutriente está inadequada. Esse número corresponde à área da curva abaixo desse valor de referência. Concluiu-se que essa nova abordagem minimiza o erro do cálculo da prevalência de inadequação de nutrientes, pois considera as características aleatórias da dieta. In assessing food intake patterns in groups of individuals, it is usually important to know how many of these individuals present nutrient intakes above or below a determined criterion. This information is relevant for planning healthcare actions, both in monitoring and in assessing such interventions, and also for the purposes of regulating commercial activities. This paper discusses a new methodology for estimating the prevalence of inadequate nutrient intake, with the Dietary Reference Intakes as the reference values. The utilization of diet surveys that allow the most accurate quantitative estimate possible is dealt with. These should use repeated measurements of food intake, on non-consecutive days. The food intake should be adjusted for between-person and within-person variance, so as to obtain a corrected distribution for the nutrient intake values. After constructing this distribution curve based on the corrected estimated parameters (average and standard deviation), the EAR method (Estimated Average Requirement) can be used as a cutoff point for verifying the proportion of individuals that has inadequate nutrient intake. This corresponds to the area of the curve below this reference value. It is concluded that this new approach minimizes the error in the calculation of the prevalence of inadequate nutrient intake, since it takes into consideration the random characteristics of the diet.